PENURUNAN LOGAM KADMIUM (CD) DALAM AIR MENGGUNAKAN ADSORBEN BERBASIS MAHKOTA NANAS - Fatiha, Nazla Zaharani; Lestari, Puji; Siswoyo, Eko (Universitas Pelita Bangsa, 2025)
Cadmium (Cd) is a heavy metal that can harm ecosystems and human health even at low concentrations. Elevated Cd levels may contaminate the food chain and cause health disorders, including kidney damage. Adsorption is considered a promising removal method due to its simplicity, efficiency, and low cost. This study investigates the potential of pineapple crown as a natural adsorbent for cadmium removal from water. A batch adsorption system was applied using non-activated pineapple crown with variations in pH, cadmium concentration, and contact time to determine optimal conditions. Humic acid was also added at different concentrations to evaluate its effect on adsorption performance. The adsorbent was characterized using FTIR and SEM, while cadmium levels were analyzed using Atomic Absorption Spectrophotometry (AAS). The findings indicate that optimal adsorption occurred at pH 7, 10 ppm Cd concentration, and 120 minutes contact time. The adsorption process followed the Langmuir isotherm and second-order kinetic model. The addition of humic acid showed an optimum response at 5%, but its influence was not significant. The maximum removal efficiency reached 88.77%, demonstrating that pineapple crown is an effective and sustainable adsorbent for Cd removal.